Measuring Management Success for Protected Species: Looking beyond Biological Outcomes - Bisack, Kathryn D.; Magnusson, Gisele M. (Frontiers in Marine Science, 2016)
The complexity of the ocean ecosystem, including the human component, is such that a single fishery may require multiple policy instruments to support recovery and conservation of protected species, in addition to those for fisheries management. As regulations multiply, the need for retrospective analysis and evaluation grows in order to inform future policy. To accurately evaluate policy instruments, clear objectives and their link to outcomes are necessary, as well as identifying criteria to evaluate outcomes. The Northeast United States sink gillnet groundfish fishery provides a case study of the complexity of regulations and policy instruments implemented under the Marine Mammal Protection Act and the Endangered Species Act to address bycatch of marine mammals. The case study illustrates a range of possible objectives for the policy instruments including biological, economic, social-normative and longevity factors. We highlight links between possible objectives, outcomes and criteria for the four factors, as well as areas for consideration when undertaking ex-post analyses. To support learning from past actions, we call for a coordinated effort involving multiple disciplines and jurisdictions to undertake retrospective analyses and evaluations of key groups of policy instruments used for protected species.